The impact of motivation towards productivity of paddy growers under management area farmers organization (PPK) Nilam Puri, Kelantan / Raja Nur Ain Raja Hussin - Raja Hussin, Raja Nur Ain (Faculty of Plantation and Agrotechnology, 2018)
Paddy crops in our country produced only for self-sufficiency Malaysians people and required import from neighboring country for about 30 %. Malaysian rice developing is still constrained by the low efficiency despite the fact that have numerous support and appropriations that have been used to this sector. Aim of this study was to identify motivation factors that influence farmer’s productivity (Act as dependent variable) based on the five (5) factors of human need (Maslow Hierarchy of Need) which is physiology need, safety need, belonging and love need, self-esteem and last factor is self-actualization. The objectives of this study are to evaluate the factors of human motivation towards the productivity of paddy growers under supervision (PPK) Nilam Puri, Kelantan and to determine the most influence factors of motivation among paddy growers. The study was focused on selected village under supervision of PPK Nilam Puri, Kelantan, where 52 respondents were identified to be asked by using questionnaire and interview. The result was analyzed using Statistical Package for Social Science (SPSS) for reliability test, descriptive, Pearson correlation and multiple linear regression analysis. The most dominant factors which is factor is love and be-longing need contributed as much as 7.40 % to the productivity of farmers and another 92.60% is caused by other factors. Overall, the organization should make regular interaction with farmers to identify their problem in production of rice. The study may give benefit to several area of researchers where it can help the farmers itself, government authority especially PPK Nilam Puri, Kelantan and the next future researcher in order to increase the production of rice by paddy growers.